Off‐campus injuries, on‐campus third‐party conduct might present potential liability under Title IX. (9th March 2022) - Lyerly, Eric
Abstract : Higher education law has long been concerned with whether colleges and universities should be held liable for student injuries that happen off campus. The law has repeatedly examined whether these institutions should be held liable when nonstudent guests inflict injuries to students on campus. These questions have often found life in tort/negligence law, where the focus is whether there is a special (legal) relationship between institutions of higher education and their students.